2020
DOI: 10.1177/0265407520953898
|View full text |Cite
|
Sign up to set email alerts
|

Romantic relationships in adults with ADHD: The effect of partner attachment style on relationship quality

Abstract: Prior literature indicates that insecure attachment styles (i.e., anxious or avoidant) and attention-deficit/hyperactivity disorder (ADHD) both have negative impacts on romantic relationships, but relatively little is known about how these factors interact among couples where one partner has ADHD and the other does not. One hundred and fifty-nine partners of adults with significant ADHD symptoms completed measures of their own attachment styles, their partner’s ADHD symptoms, and relationship quality. Anxious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…Indeed, across all three life domains studied (i.e., interpersonal relationships, employment, and mental health), we found that ADHD symptoms were a robust predictor of life outcomes in early middle adulthood. In particular, consistent with previous research ( Combs et al, 2015 ; Knies et al, 2021 ; Painter et al, 2008 ), we found that inattention and hyperactivity-impulsivity symptoms were robust predictors of life success when being predicted both concurrently and prospectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, across all three life domains studied (i.e., interpersonal relationships, employment, and mental health), we found that ADHD symptoms were a robust predictor of life outcomes in early middle adulthood. In particular, consistent with previous research ( Combs et al, 2015 ; Knies et al, 2021 ; Painter et al, 2008 ), we found that inattention and hyperactivity-impulsivity symptoms were robust predictors of life success when being predicted both concurrently and prospectively.…”
Section: Discussionsupporting
confidence: 91%
“…In the domain of interpersonal relationships, studies have repeatedly found greater ADHD symptomatology to be associated with poorer relationship quality ( Bodalski et al, 2019 ; Bruner et al, 2015 ; Knies et al, 2021 ). In particular, a recent study by Knies et al (2021) found that overall ADHD symptoms were negatively associated with overall relationship satisfaction and positively associated with perceived partner neglect and threat. Similarly, Bruner et al (2015) found that adults with clinically significant levels of overall ADHD symptoms had poorer relationship quality than adults without clinically significant ADHD symptoms.…”
Section: Adhd In Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this framework, as a core component of personality, IWMs would impact a range of psychological functioning domains such as emotion regulation capacities or interpersonal functioning (Bowlby, 1969(Bowlby, , 1973. A key life domain that is greatly impacted is romantic interpersonal functioning (Knies et al, 2021), with several authors stating that the quality of romantic relationships is rooted in the vicissitudes of early attachment experiences (Owens et al, 1995;Roisman et al, 2005;Velotti et al, 2014).…”
Section: Adult Attachment and Romantic Relationshipsmentioning
confidence: 99%
“…To support healthy relationships, it is important to understand the predictors of relationship quality for individuals and their partners. Attachment is repeatedly identified as key predictor of relationship quality [19][20][21][22], relationship satisfaction [23,24], commitment [25,26], intimacy [27,28], sexual satisfaction [29,30], marital adjustment [31], and relationship stability [32,33]. There is also a link between attachment insecurities and poor coping skills [34,35], more perceived conflict [36], negative affect [37], pessimistic attribution [38], and relationship distress [39].…”
Section: Introductionmentioning
confidence: 99%